Adverse pregnancy outcomes and infant mortality after quadrivalent HPV vaccination during pregnancy. Issue 2 (7th January 2019) - Faber, Mette Tuxen; Duun-Henriksen, Anne Katrine; Dehlendorff, Christian; Tatla, Manrinder Kaur; Munk, Christian; Kjaer, Susanne K.
Highlights: There was no association between HPV vaccination and the risk of spontaneous abortion. There was no association between HPV vaccination and the risk of stillbirth. There was no association between HPV vaccination and one-year mortality. Abstract: Background: Few studies have studied the association between unintended human papillomavirus (HPV) vaccination and adverse pregnancy outcomes. This study set out to determine the association between HPV vaccination during pregnancy and subsequent risk of spontaneous abortion, stillbirth, and one-year infant mortality. Methods: Population-based study including all pregnancies in Denmark (October 2006–December 2014) among women born 1975–1992. From nationwide health registries using the personal identification numbers, we obtained information on HPV vaccination, pregnancy outcomes, and infant mortality. The exposure window went from four weeks before conception date until 22 weeks of gestation for the outcome spontaneous abortion, and until birth for stillbirth and infant mortality outcomes. In the analyses of spontaneous abortion, we used time to event models, for stillbirth logistic regression models, and for infant mortality Cox regression was applied. Results: We included 522, 705 pregnancies for the outcome spontaneous abortion (7487 exposed to at least one dose during pregnancy); 351, 878 births (5262 exposed to at least one dose during pregnancy) for the stillbirth; and 350, 739 live births (5245 exposed to at least one dose during pregnancy) for infant mortality. No significantly increased rate of spontaneous abortion among women vaccinated during pregnancy compared with unvaccinated women was found. In addition, we found no association between HPV vaccination during pregnancy and stillbirth (adjusted odds ratio = 0.96 [95% CI: 0.57–1.61]), or infant mortality (adjusted hazard ratio = 0.94 [95% CI: 0.53–1.67]). A secondary analysis showed no association between number of doses and timing of administration (i.e. vaccination before or during pregnancy) and an increased risk of spontaneous abortion. Conclusion: We found no increased risk of spontaneous abortion, stillbirth, or infant mortality following unintended HPV vaccination during pregnancy.